Postbiotic nasal priming improves of innate immune response in respiratory mucosa-associated lymphoid tissue in malnourished mice - Ivir, Héctor Maximiliano (2022)
The nasal priming of malnourished mice with the peptidoglycan (PG) of Lacticaseibacillus rhamnosus CRL1505 (Lr) is as effective as viable strain for improving systemic and respiratory immune response against Streptococcus pneumoniae (Sp). But the impact of these treatments on mucosa-associated lymphoid tissue is unknown. Hence, the effect of nasal administration of Lr or PG on the innate immune response of nasopharynx-associated lymphoid tissue (NALT) and cervical lymph nodes (CLN) in malnourished mice under repletion treatments was evaluated. Weaned Swiss mice were malnourished with a protein-free diet (PFD) for 21d. Malnourished mice received a balanced conventional diet (BCD) during 7d (BCD group) or BCD with nasal supplementation with Lr (108 cells/mouse/d) or PG (8 µg/mouse/d) during the last 2d of treatment (Lr or PG groups). Malnourished control mice (MNC) received PFD while the well-nourished control group (WNC) consumed BCD. On d8, all groups were infected with Sp (107 cells/mouse). Before infection, MNC showed a significant decrease of the total cells, T and B lymphocytes in NALT and CLN as well as the macrophages, myeloid and dendritic cells in NALT. In addition, the MNC showed an increase of NALT Gr-1+ cells % and the microbial load in nasal washes. BCD treatment was not able to normalize these parameters. However, the Lr and PG groups improved the total cells, B and T cells counts in NALT and CLN. Challenge with Sp increased the numbers of neutrophils and macrophages and TNF-α, INF-γ, IL-6, IL17 and IL-10 levels in nasal washes. The values were lower in MNC than in WNC. However, unlike the BDC group, Lr and PG groups showed values of NALT phagocytes, and lymphocytes, T CD4+ cells in CLN and NALT similar to WNC mice. Moreover, IL-6, INF-γ and TNF-α levels in nasal washes were higher in Lr or PG groups. NALT is a target for postbiotics administration to improve respiratory immunity in immunocompromised malnourished hosts.